CHMP4C: A novel regulator of the mitotic spindle checkpoint - Petsalaki, Eleni (Mol Cell Oncol, 2018)
The mitotic spindle checkpoint delays anaphase onset until all chromosomes have achieved stable kinetochore-microtubule attachments. Here, we discuss recent findings showing that CHMP4C, a component of the endosomal sorting complex required for transport (ESCRT) machinery, protects human cells against chromosome missegregation by promoting localisation of the ROD–ZW10–ZWILCH (RZZ) spindle checkpoint complex to unattached kinetochores.